The mythical structure and bridging of functions A nominal reading in the poetry of KhazalMajidi - et. al., Riyadh KareemAbdullah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Interconnectednessin the cultural center of the poetic text of Khazaal al-Majidi embodies the actions of the focus of differentiation in employing the myth, and it connects at the other end to the possible rays of what the mythical event is, right up to the poetic dramatization of that event in the text, so that the mythical character becomes the focus of the poet’s attention, poetic employment from the point of view of the format implicit represents a formats own culture poet mm of making the choice myth employee tends to favor the poetic vision of the poet Majidi Although Tmahiaa with methods of recruitment of myth in contemporary poem, making the opening of the text of poetic commonplace and acceptable in the architectural light the modern poem , is not too much that we went to that all the formats that have appeared in this chapter or the next chapters later in the poetry Majidi her mythological roots, identifies with Alostor of mother sometimes approaching, moving away altogether, but the result is orbiting the legend, and draw Its manifestations and existence came from the womb of the myths that lived in the poet's imagination.